Answer:
[tex]\begin{aligned} \frac{dy}{dx} &= \frac{\cos(t) + \sin(t)}{\cos(t) - \sin(t)} \end{aligned}[/tex] given that [tex]a \ne 0[/tex] and that [tex]\cos(t) - \sin(t) \ne 0[/tex].
Step-by-step explanation:
The relation between the [tex]y[/tex] and the [tex]x[/tex] in this question is given by parametric equations (with [tex]t[/tex] as the parameter.)
Make use of the fact that:
[tex]\begin{aligned} \frac{dy}{dx} = \quad \text{$\frac{dy/dt}{dx/dt}$ given that $\frac{dx}{dt} \ne 0$} \end{aligned}[/tex].
Find [tex]\begin{aligned} \frac{dx}{dt} \end{aligned}[/tex] and [tex]\begin{aligned} \frac{dy}{dt} \end{aligned}[/tex] as follows:
[tex]\begin{aligned} \frac{dx}{dt} &= \frac{d}{dt} [a\, (\cos(t) + \sin(t))] \\ &= a\, (-\sin(t) + \cos(t)) \\ &= a\, (\cos(t) - \sin(t))\end{aligned}[/tex].
[tex]\begin{aligned} \frac{dx}{dt} \ne 0 \end{aligned}[/tex] as long as [tex]a \ne 0[/tex] and [tex]\cos(t) - \sin(t) \ne 0[/tex].
[tex]\begin{aligned} \frac{dy}{dt} &= \frac{d}{dt} [a\, (\sin(t) - \cos(t))] \\ &= a\, (\cos(t) - (-\sin(t))) \\ &= a\, (\cos(t) + \sin(t))\end{aligned}[/tex].
Calculate [tex]\begin{aligned} \frac{dy}{dx} \end{aligned}[/tex] using the fact that [tex]\begin{aligned} \frac{dy}{dx} = \text{$\frac{dy/dt}{dx/dt}$ given that $\frac{dx}{dt} \ne 0$} \end{aligned}[/tex]. Assume that [tex]a \ne 0[/tex] and [tex]\cos(t) - \sin(t) \ne 0[/tex]:
[tex]\begin{aligned} \frac{dy}{dx} &= \frac{dy/dt}{dx/dt} \\ &= \frac{a\, (\cos(t) + \sin(t))}{a\, (\cos(t) - \sin(t))} \\ &= \frac{\cos(t) + \sin(t)}{\cos(t) - \sin(t)}\end{aligned}[/tex].